Christianity and empire in South Manipur Hills : Senvon encounter and the dialogic Zo peoples - Ngaihte, Samuel (Samuel G.); Paulianding, Reuben (Regnum studies in mission., 2022)
"This book contextually examines the advent of Christianity in South Manipur Hills, North-East India, within the larger framework of British colonial intrusions upon the Zo world. It explores the internal rationale that informs the reception, appropriation, and institutionalisation of the Christian narrative through a hermeneutical reading of the Senvon-encounter between the missionaries and the Zo communities as a site of dialogic meeting and negotiation. The authors postulate the importance of the agency of host communities as a site of contextual enquiry which has methodological and substantive insights, both for the theological discourse on contextualisation, and the self-understanding of the Zo peoples."--Publisher.